Privacy issues and management in the National Library Board (Singapore) - Wang, Damien Khang Cheh (2008)
The Library 2000 report identified technology as one of the three key enablers of the Library 2000 Review Committee's recommendations. Since its formation in 1995, NLB had received accolades for its innovative use of information technology (IT), i.e. library automation and online/e-commerce services. While privacy was largely a peripheral concern for many in Singapore, a vocal minority had voiced concerns about privacy-related issues such as unauthorised usage of membership accounts and cards.The literature review surfaced various threats to patron privacy such as poor location of Internet terminals and third-party usage tracking, and established that privacy concerns do affect online transactions. However, these fears could be mitigated by factors such as good privacy management policies implemented by service providers and the availability of coping strategies on the part of consumers. A total of eleven methods used to manage privacy issues were surfaced, including governmenr legislation, industry self-regulation, non-government watchdogs and software solutions such as anonymous browsing tools. The literature review also covered roles played by libraries and librarians, e.g. in systems design and in public education.